Energy Trade Amidst Sustainable Economic Growth in Regional Cooperation of West African States: Fresh Evidence from Panel CS-ARDL - Atiku, Abubakar Mohammed; Ismail, Suraya; Ahmad, Ali Umar (International Journal of Energy Economics and Policy, 2021)
This study aims to examine the influence of energy trade, energy use, and carbon emission on economic growth for the period of 1970-2019, in regional cooperation of West African states. This study employed second generation techniques. The results revealed that energy trade increased economic growth in the long run. However, in short run energy trade reduced in economic growth. Besides, energy consumption impeded the economic growth in both short run and long run, while carbon emission increased the economic growth in both short run and long run. The energy crisis of 2014 decreased economic growth. Moreover, the result of interaction term of energy consumption and carbon emission showed positive influence on economic in both short run and long run. In addition, the results of causality showed uni-directional causal relationship from energy trade to economic growth. Policy recommendations can be made, in the sense that policies should be geared towards promoting renewable sustainable energy conservation policy that could possibly improve economic integration. Keywords: Economic Growth, Energy Trade, Regional Cooperation of West African States, Second Generation Techniques JEL Classifications: F34, K32, O55, C01 DOI: https://doi.org/10.32479/ijeep.11598